Analyzing Entertainment Tax Impact on Batu City's Regional Revenue and Taxpayer Compliance Levels - Monadi, Elisabet Juwita (University of Merdeka Malang, 2024)
Entertainment tax is one of the sources of revenue for local governments. This study aims to examine the contribution of entertainment tax to Regional Original Revenue (PAD) in Batu City. The research method used is qualitative descriptive using object data at the Batu City Regional Finance Agency. Based on data from the Central Statistics Agency (BPS), Batu City's tax financial statements from 2020 to 2022 are tax revenues for the entertainment sector. In 2020, the contribution reached 12.42%, while in 2021, the contribution decreased to 8.89% and in 2022, the contribution decreased to 12.78%. Although the data has decreased and increased, it shows that the entertainment tax in Batu City has a lack of contribution to the Regional Original Revenue (PAD). The government needs to monitor the potential of taxes and conduct socialization so that this contribution can increase. In order to increase the effectiveness of entertainment tax revenue, the Batu City Regional Revenue Office needs to provide socialization to the public regarding entertainment tax rates and calculation methods.Â Â